The role of play activities in the formation of moral behavior in younger schoolchildren (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
Today, the education system pays special attention to the development of the child’s personality. Students entering school for the first time are involved in a new sphere of social life and behavior. The formation of their moral qualities is a common responsibility of teachers, parents and society. The teacher can use various methods in this direction, but of these, the game is the closest and most effective tool for the inner world of the child. This article shows the importance of the formation of moral behavior in younger schoolchildren and the role of play in this process, the educational possibilities of the game and the ways of its practical application.
Keywords: elementary school students, moral behavior, play activities, education